Communication Audit as a Barometer for the Effectiveness of Indonesian Tourism Information Dissemination - Devi Wening Astari; Bela Fataya Azmi (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
The dissemination of information or publications with clear messaging and appropriate media selection is crucial. This research evaluates the dissemination of information or publications and the choice of communication media by the Ministry of Tourism and Creative Economy through their Instagram account @kemenparekraf.id, to ascertain its accessibility and comprehensibility across all sectors of society. To address this issue, the researcher employed the evaluative audit method using content analysis and readability study design. The selected audit method was Taylor's cloze test procedure. Â Data collection involved distributing questionnaires based on the selected publication texts or captions related to the â€œBangga Berwisata di Indonesiaâ€ (BBWI) with the hashtag #DiIndonesiaAja. Research respondents included both followers and non-followers of @kemenparekraf.id on Instagram, selected through accidental sampling technique, amounting to a sample size of 100 respondents. This study found that the average readability score for the first caption was 35%, indicating the text was difficult to understand, while the second caption scored 50%, indicating moderate to understand. These findings suggest that readability levels remain low and need improvement. Efforts are necessary from the communication bureau or content creators to prioritize audience diversity, choose language that is easily understandable by all societal segments, add content aligned with the promoted programs, enhance creativity in content posts, and begin fostering two-way communication to their audience.